2012
DOI: 10.1002/cncr.27895
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of serum exosomal microRNA‐21 as a clinical biomarker in human esophageal squamous cell carcinoma

Abstract: BACKGROUND: Exosomes are 40-nm to 100-nm membrane vesicles that are secreted by various cells, and they play a major role in cell-cell communication. The objective of this study was to clarify the significance of the levels of microRNA in exosomes extracted from the sera of patients with esophageal squamous cell cancer (ESCC). METHODS: The authors isolated exosomes in serum samples from patients who had ESCC and from patients who had benign diseases without systemic inflammation. Total RNA was purified from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
272
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(289 citation statements)
references
References 35 publications
13
272
0
1
Order By: Relevance
“…Unique nucleic acids (mutant mRNA such as the epidermal growth factor receptor EGFRvIII variant) contained in exosomes could potentially serve as reliable biomarkers for glioblastoma (43). Enriched and specific miRs in exosomes may also inform diagnosis and serve to monitor the progression of cancer (16,(44)(45)(46)(47)(48). For example, exosomal miR-21 is increased in the serum of patients with esophageal squamous cell carcinoma and correlates with advanced disease stage (45).…”
Section: R E V I E W S E R I E S : E X T R a C E L L U L A R V E S I mentioning
confidence: 99%
“…Unique nucleic acids (mutant mRNA such as the epidermal growth factor receptor EGFRvIII variant) contained in exosomes could potentially serve as reliable biomarkers for glioblastoma (43). Enriched and specific miRs in exosomes may also inform diagnosis and serve to monitor the progression of cancer (16,(44)(45)(46)(47)(48). For example, exosomal miR-21 is increased in the serum of patients with esophageal squamous cell carcinoma and correlates with advanced disease stage (45).…”
Section: R E V I E W S E R I E S : E X T R a C E L L U L A R V E S I mentioning
confidence: 99%
“…However, the existing biomarkers, such as cancer-associated antigens, and proteomics analysis are unsatisfactory for the early stages of NSCLC. By contrast, recent studies have demonstrated that specific expression profiles of circulating exosomal miRNAs could be promising biomarkers for the detection of early-stage cancer and for predicting prognosis in various types of cancers (19)(20)(21). However, previous studies in NSCLC have not examined exosomal miRNAs, which could be expected to include the intact miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Robust studies evaluating circulating exosomal miRNAs signatures in esophageal cancer are yet to be reported, with the only recent studies limited to either esophageal squamous cell carcinoma cell lines, or a very small clinical cohort (eight individuals with esophageal adenocarcinoma vs. four controls) in which a broad discovery approach was not applied [13][14][15]. Hence, to evaluate the potential for circulating miRNAs in exosomes to be used as biomarkers for esophageal adenocarcinoma, we applied a broader discovery approach to investigate levels of circulating exosomal miRNAs in serum from individuals with esophageal adenocarcinoma, compared to non-dysplastic Barrett's esophagus and age-matched controls.…”
Section: Introductionmentioning
confidence: 99%